Heavy metals in composted municipal waste: Insights into environmental and human health risks in developing regions (case study: Isfahan, Iran) - Fereshteh Talebi; Farzaneh Mohammadi; Sepideh Sadeghi; Ahmad Reza Taghipour; Amir Hossein Nafez (Results in Engineering)
Compost quality, especially Heavy Metal (HMs) content, can induce harmful health impacts and environmental concerns. The purpose of this research was to evaluate the quality of compost and risk assessment of the health risk resulting from HMs exposure in compost. 41 composite samples were gathered on compost application in urban parks for measurement of physicochemical parameter and concentration of HMs. Aside from that, Monte Carlo simulation-based health risk assessment was also employed for carcinogenic and non-carcinogenic risk estimation of HMs upon accidental intake of compost. In spite of the electrical conductivity values (4.32±0.59 dS/m) within the normal limit (<8 dS/m), compost application was limited because of low germination index (55.66±18.45). The average HMs concentrations were 58.37±36.43, 5.83±11.32, 16.81±3.89, 321.38±99.10, 2.12±0.79, 157.55±47.57 and 20.77±4.86 mg/kg DW for lead, cadmium, nickel, zinc, cobalt, copper and chromium, respectively. The median values of hazard index (HI) were lower in the following order: Pb>Cd>Cr. Carcinogenic risk values of all metals in children were below 10 − 6, which indicates that there was no carcinogenic risk of these metals in children. However, carcinogenic risk estimates of compost transport workers and gardeners in the park were higher than the safe value (1×10 − 6) and they are of high potential health hazard. Based on health risk estimation, non-carcinogenic hazards were negligible for all groups, while the total carcinogenic hazard cannot be eliminated. The risk variables most vulnerable to impact on the risk index are ingestion rate, Pb concentration and exposure frequency, respectively.